Centrifugal Pumping Force in Oil Injection-Based TMS to Cool High-Power Aircraft Electric Motors - Giuseppe Di Lorenzo; Diego Giuseppe Romano; Antonio Carozza; Antonio Pagano (Energies)
One of the challenges of our age is climate change and the ways in which it affects the Earth’s global ecosystem. To face the problems linked to such an issue, the international community has defined actions aimed at the reduction in greenhouse gas emissions in several sectors, including the aviation industry, which has been requested to mitigate its environmental impact. Conventional aircraft propulsion systems depend on fossil fuels, significantly contributing to global carbon emissions. For this reason, innovative propulsion technologies are needed to reduce aviation’s impact on the environment. Electric propulsion has emerged as a promising solution among the several innovative technologies introduced to face climate change challenges. It offers, in fact, a pathway to more sustainable air travel by eliminating direct greenhouse gas emissions, enhancing energy efficiency. Unfortunately, integrating electric motors into aircraft is currently a big challenge, primarily due to thermal management-related issues. Efficient heat dissipation is crucial to maintain optimal performance, reliability, and safety of the electric motor, but aeronautic applications are highly demanding in terms of power, so ad hoc Thermal Management Systems (TMSs) must be developed. The present paper explores the design and optimization of a TMS tailored for a megawatt electric motor in aviation, suitable for regional aircraft (~80 pax). The proposed system relies on coolant oil injected through a hollow shaft and radial tubes to directly reach hot spots and ensure effective heat distribution inside the permanent magnet cavity. The goal of this paper is to demonstrate how advanced TMS strategies can enhance operational efficiency and extend the lifespan of electric motors for aeronautic applications. The effectiveness of the radial tube configuration is assessed by means of advanced Computational Fluid Dynamics (CFD) analysis with the aim of verifying that the proposed design is able to maintain system thermal stability and prevent its overheating.